A Practical Framework for Understanding and Reducing Medical Overuse: Conceptualizing Overuse Through the Patient‐Clinician Interaction. Issue 5 (1st May 2017) - Morgan, Daniel J.; Leppin, Aaron L.; Smith, Cynthia D.; Korenstein, Deborah
Abstract : Overuse of medical services is an increasingly recognized driver of poor‐quality care and high cost. A practical framework is needed to guide clinical decisions and facilitate concrete actions that can reduce overuse and improve care. We used an iterative, expert‐informed, evidence‐based process to develop a framework for conceptualizing interventions to reduce medical overuse. Given the complexity of defining and identifying overused care in nuanced clinical situations and the need to define care appropriateness in the context of an individual patient, this framework conceptualizes the patient–clinician interaction as the nexus of decisions regarding inappropriate care. This interaction is influenced by other utilization drivers, including healthcare system factors, the practice environment, the culture of professional medicine, the culture of healthcare consumption, and individual patient and clinician factors. The variable strength of the evidence supporting these domains highlights important areas for further investigation.